Food tables & labelling - Bender, Arnold E. [ (Arnold Eric)]; Bender, David A. (Oxford, New York : Oxford University Press, 1998)
Students of all levels studying home economics, food technology, chemistry, biology, or any subject that involves nutrition and food science will find Food Tables and Labelling an invaluable resource
1. The need for food: energy and protein -- 2. The need for food: vitamins and minerals -- 3. The nutrient content of foods -- 4. Alcoholic beverages -- 5. Food labelling -- 6. Height, weight and growth -- 7. Miscellaneous tables
Previous ed. published in 2v. as: Food tables. 1986 - Food labelling. 1991
Keywords: Food -- Composition -- Tables; Food -- Labeling -- Great Britain